Sociocultural barriers to hepatitis B health literacy in an immigrant population: a focus group study in Korean Americans - Sarah Hyun; Okhyun Ko; Soonsik Kim; William R. Ventura (BMC, 2021)
Abstract Background Chronic hepatitis B (CHB) is a major global health issue disproportionately affecting Asian Americans and other immigrant populations in the United States. Despite the high risk of morbid complications from CHB, the majority of individuals with CHB do not access healthcare due to a complex of barriers. These barriers influence health literacy which may affect behaviors linked to hepatitis B care. We aimed to identify and evaluate various sociocultural factors and how they interact with health literacy to impact CHB care and health seeking in a Korean American population. Methods A total of 28 Korean American individuals with CHB were divided into 5 different focus discussion groups. This study investigated the participants' sociocultural backgrounds as well as their awareness and utilization of the healthcare system that could influence their health literacy and behaviors in accessing care. Results Our analysis identified and concentrated on three themes that emerged from these discussions: low risk perception and knowledge of CHB and its complications; language, immigrant status, and stigma; and financial and institutional barriers. The participants' overall awareness of the disease and prevention methods demonstrated poor understanding of important characteristics and potential outcomes of the disease. Additionally, differences in cultural expectations and a lack of understanding and utilization of healthcare systems affected health literacy in further limiting participants' motivation to seek care. Conclusions The present study suggests that there are culture-specific barriers to health literacy governing individuals' health behavior in accessing hepatitis B care. These findings may inform strategies for developing culturally tailored resources and programs and for facilitating the implementation of community-wide hepatitis B education and screening initiatives in immigrant communities.